Competitive Exclusion Prevents Colonization and Compartmentalization Reduces Transmission of ESBL-Producing Escherichia coli in Broilers - Dame-Korevaar, Anita; Kers, Jannigje G.; van der Goot, Jeanet; Velkers, Francisca C.; Ceccarelli, Daniela; Mevius, Dik J.; Stegeman, Arjan; Fischer, Egil A. J. (Frontiers in Microbiology, 2020)
Extended spectrum β-lactamase (ESBL)-producing bacteria are resistant to extended-spectrum cephalosporins and are common in broilers. Interventions are needed to reduce the prevalence of ESBL-producing bacteria in the broiler production pyramid. This study investigated two different interventions. The effect of a prolonged supply of competitive exclusion (CE) product and compartmentalization on colonization and transmission, after challenge with a low dose of ESBL-producing Escherichia coli, in broilers kept under semi-field conditions, were examined. One-day-old broilers (Ross 308) (n=400) were housed in four experimental rooms, subdivided in one seeder (S/C1)-pen and eight contact (C2)-pens. In two rooms, CE product was supplied from day 0 to 7. At day 5, seeder-broilers were inoculated with E. coli strain carrying blaCTX-M-1 on plasmid IncI1 (CTX-M-1-E. coli). Presence of CTX-M-1-E. coli was determined using cloacal swabs (day 5-21 daily) and cecal samples (day 21). Time until colonization and cecal excretion (log10 CFU/g) were analyzed using survival analysis and linear regression. Transmission coefficients within and between pens were estimated using maximum likelihood. The microbiota composition was assessed by 16S ribosomal RNA gene amplicon sequencing in cecal content of broilers on days 5 and 21. None of the CE broilers was CTX-M-1-E. coli positive. In contrast, in the untreated rooms 187/200 of the broilers were CTX-M-1-E. coli positive at day 21. Broilers in C2-pens were colonized later than seeder-broilers (Time to event Ratio 3.53, 95% CI 3.14 – 3.93). The transmission coefficient between pens was lower than within pens (3.28×10-4 day-2, 95% CI 2.41×10-4 – 4.32×10-4 versus 6.12×10-2 day-2, 95% CI 4.78×10-2 – 7.64×10-2). The alpha diversity of the cecal microbiota content was higher in CE broilers than in control broilers at days 5 and 21. The supply of a CE product from day 0 to 7 prevented colonization of CTX-M-1-E. coli after challenge at day 5, likely as a result of CE induced effects on the microbiota composition. Furthermore, compartmentalization reduced transmission rate between broilers. Therefore, a combination of compartmentalization and supply of a CE product may be a useful intervention to reduce transmission and prevent colonization of ESBL/pAmpC-producing bacteria in the broiler production pyramid.